Transforming waste management methods: a Dutch Airport’s journey toward a circular economy through baseline measurements and strategic priority setting - van der Tuin-Rademaker, Anne; Tschavgova, Elisabeth; van Maaren, Christian; Solis, Sara; Campisano, Saro; van Dam, Sonja (Frontiers in Sustainability, 2024)
Airports, the essential hubs of global travel, have to cater for the increasing demands for air travel, with growing passenger numbers and the associated growth in resource consumption. While the aviation sector prioritizes reducing environmental impact in the air, substantial waste is generated at airports. This necessitates a critical examination of waste management practices, especially since a Circular Economy (CE) approach is gaining momentum within the aviation sector. This article introduces the Baseline Circular Airports Method (BCAM), a methodology developed and rigorously tested at Schiphol Amsterdam Airport. BCAM systematically analyzes resource streams, considering composition and relevant stakeholders, treatment processes, and environmental impact. By doing so, it establishes strategic prioritization of resource streams for airports to perform focused and effective interventions. BCAM analysis reveals that the highest impact of operational resource streams are Residual, Plastic, Swill, Paper, and International Catering Waste (CAT1), and that corresponding waste management efficiencies can be determined. These outcomes serve as a baseline for ongoing monitoring, offering airports a starting point for strategic planning and assessing progress towards sustainable waste management and CE transitions.